Regional Collaboration on Education : An ARAIEQ Innovation - Thacker, Simon; Moreno, Juan Manuel (World Bank, Washington, DC, 2015)
This Knowledge and Learning Note discusses regional collaboration on education in the Arab world. Regional collaboration on Education is arguably more challenging, comparatively speaking, in the Arab World than in other regions of the world. There are many reasons for this which this brief spells out. In education, it is true the Middle East and North Africa (MENA) region had initially made great strides after Independence in improving access, equity, and completion outcomes. However, as far as regional collaboration on education is concerned, national policymakers largely worked to address domestic concerns alone with only little external assistance, mostly because the education sector was considered to be entwined in national interest and identity. This brief offers current trends and examples of the state of education in the MENA region including examples of programs and main focal points to achieve higher educational standards.